Determining quality requirements at the universities to improve the quality of education (Journal of Economic Research & Business Administration, 2018)
In this study the information was given regarding Kano’s Model and a case study was conducted for universitystudents. Kano’s Model was applied for Akhmet Yassawi University students and it was questioned whatthey thought were important quality requirements in higher education, the degree of their importance and howthey evaluated their own institutions with respect to the quality requirements. The purpose of this study is to determinethe student requirements regarding the quality of the undergraduate programs of Tourism Managementand Finance in Akhmet Yassawi University and to analyze the student satisfaction and dissatisfaction and theirmajority roles in determining and improving the quality of the programs. To achieve this object, firstly Kano’sSurvey was applied to 116 students and the student requirements relating to the education were uncovered byfocusing on group work. Secondly, these requirements were classified by Kano Evaluation Table. Thus, the qualityrequirements divided into four categories: must-be, one-dimensional, attractive and indifferent. Finally, thevalues of satisfaction and dissatisfaction were calculated and the roles of these requirements in increasing anddecreasing student satisfaction and dissatisfaction were identified clearly